Wykonaj działania:
b) (5x^3 - 6x)^2
c) (3x^7 + 2x)^2
d) (9x^7 - x^3 ) (9x^7 + x^3)
b)(5x^3 - 6x)^2=25 x^6-60 x^4+36 x^2
c)(3x^7 + 2x)^2=9 x^14+12 x^8+4 x^2
d)(9x^7 - x^3 ) (9x^7 + x^3)= 81 x^14-x^6
b)
c)
d)
PS:
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
b)(5x^3 - 6x)^2=25 x^6-60 x^4+36 x^2
c)(3x^7 + 2x)^2=9 x^14+12 x^8+4 x^2
d)(9x^7 - x^3 ) (9x^7 + x^3)= 81 x^14-x^6
b)![(a-b)^2=a^2-2ab+b^2\\ (5x^3 - 6x)^2=(5x^3)^2 -2\cdot5x^3\cdot6x+ (6x)^2=25x^6-60x^4+36x^2 (a-b)^2=a^2-2ab+b^2\\ (5x^3 - 6x)^2=(5x^3)^2 -2\cdot5x^3\cdot6x+ (6x)^2=25x^6-60x^4+36x^2](https://tex.z-dn.net/?f=%28a-b%29%5E2%3Da%5E2-2ab%2Bb%5E2%5C%5C+%285x%5E3+-+6x%29%5E2%3D%285x%5E3%29%5E2+-2%5Ccdot5x%5E3%5Ccdot6x%2B+%286x%29%5E2%3D25x%5E6-60x%5E4%2B36x%5E2+)
c)![(a+b)^2=a^2+2ab+b^2 (a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
d)![(a-b)(a+b)=a^2-b^2\\ (9x^7 - x^3 ) (9x^7 + x^3)=(9x^7)^2 - (x^3 )^2=81x^{14}-x^6. (a-b)(a+b)=a^2-b^2\\ (9x^7 - x^3 ) (9x^7 + x^3)=(9x^7)^2 - (x^3 )^2=81x^{14}-x^6.](https://tex.z-dn.net/?f=%28a-b%29%28a%2Bb%29%3Da%5E2-b%5E2%5C%5C+%289x%5E7+-+x%5E3+%29+%289x%5E7+%2B+x%5E3%29%3D%289x%5E7%29%5E2+-+%28x%5E3+%29%5E2%3D81x%5E%7B14%7D-x%5E6.)
PS:![(x^a)^b=x^{a\cdot b}\\ x^a\cdot x^b=x^{a+b} (x^a)^b=x^{a\cdot b}\\ x^a\cdot x^b=x^{a+b}](https://tex.z-dn.net/?f=%28x%5Ea%29%5Eb%3Dx%5E%7Ba%5Ccdot+b%7D%5C%5C+x%5Ea%5Ccdot+x%5Eb%3Dx%5E%7Ba%2Bb%7D)